Correlation between Inflammatory Markers of Platelet Index and Vitamin D with Body Mass Index - Grace Yuni Harviendo; Ariosta Ariosta; Meita Hendrianingtyas (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2022)
Weight loss is more of a worldwide health problem and a risk factor for chronic disease. The decrease in serum vitamin D levels in body weight leads to more low grade inflammation. This study aims to determine the relationship between the platelet index, namely MPV, P-LCR as a marker of inflammation and vitamin D with body mass index (BMI). This study was a cross-sectional study of 78 women at the Diponegoro National Hospital with overweight (BMI> 23) in July - September 2020. Data analysis was done using Pearson and Spearman tests and significant if p <0.05. Of the 78 research samples, there was a significant relationship between BMI and MPV (r = 0.404; p = 0.000); P-LCR (r = 0.425; p = 0.000) and 25 (OH) D (r = -0.231; p = 0.04). Low vitamin D levels in obesity and low-grade inflammation increase pro-inflammatory cytokines. Increased leptin levels in obesity contribute to platelet hyperreactivity. Increased platelet activity compensates for the platelets so that the MPV and P-CLR values increase. There is a moderate significant positive relationship between MPV, P-CLR and BMI and a weak significant negative relationship between 25 (OH) D and BMI.